Effects of Acidic Polysaccharide-Enriched Extracts from Holothuria tubulosa on Two- and Three-Dimensional Invasive Breast Cancer Cell Models - Cristina Ciampelli; Sylvia Mangani; Gabriele Nieddu; Marilena Formato; Paraskevi Ioannou; Spyros Kremmydas; Nikos Karamanos; Antonio Junior Lepedda (Biology)
Marine invertebrates, particularly Holothurians, have emerged as valuable sources of bioactive compounds with potential anticancer properties. In this study, we investigated the effects of two acidic polysaccharide-enriched (APs) fractions (Ht1 and Ht2) from the sea cucumber species Holothuria tubulosa on the highly invasive cell line MDA-MB-231. Functional assays were performed to assess cell viability, migratory potential, adhesion on collagen I, and cell morphology, alongside gene expression analysis. Additionally, a preliminary evaluation of their effects on three-dimensional breast cancer cell-derived spheroids was conducted. Both AP fractions exerted anticancer effects by decreasing cell viability. Ht1 showed a significant inhibitory effect on cell migration, increased adhesion on collagen I, and exhibited a trend to transform the mesenchymal MDA-MB-231 cells to a more epithelial phenotype. Treatment with the AP fractions modulated the expression of genes, such as the epithelial marker E-cadherin (for the Ht1), a key cell adhesion molecule, and the matrix metalloproteinases 7 and 9 (for the Ht2), enzymes involved in extracellular matrix remodeling, which hold critical roles in cancer progression and metastasis. No significant effects were observed on spheroids, possibly due to the high charge and hydrophilicity of the APs, leading to poor penetration into the inner spheroid layers. Although preliminary, these findings highlight the potential of H. tubulosa-derived APs as promising antineoplastic agents, warranting further investigation into their mechanisms of action and structural characterization.